ENTOPHARMACOLOGICAL STUDY OF CANDLENUT PLANT (ALEURITES MOLUCCANA L.) AS A TREATMENT FOR BANJAR COMMUNITY DISEASE - Siti Shalihah; Sari Indriyani; Meyninda Destiara; Norfajrina (RADJA PUBLIKA, 2025)
Candlenut plants also known as keminting have various benefits for the Banjar community, especially in the fields of health, economy, and culture. However, its use in the perspective of ethnobotany based on local wisdom has not been widely studied, especially in the pharmacological aspect. This study aims to analyze the use of candlenut plants as natural medicine in Banyu Irang Village, South Kalimantan. The research method was snowball sampling with data collection techniques through observation, semi-structured interviews, and documentation. Ethnopharmacologically, various parts of the candlenut plant, such as roots, stems, leaves, and seeds, have long been used in traditional medicine. Candlenut oil is used for hair care and skin health, while the boiled water of the leaves is used to improve digestion and help the body's detoxification process. Local communities still maintain this practice for generations as part of their cultural heritage. In addition to its health benefits, candlenut also has economic potential as a raw material for the pharmaceutical, cosmetic, and herbal industries. However, its utilization and on-site management are still limited, so efforts are needed to improve cultivation and crop processing innovations to optimize its economic benefits. The results of this study are expected to support efforts to conserve candlenut plants while maintaining the local wisdom values of the Banyu Irang Village community. In addition, further studies on the ethnobotanical aspects and potential commercialisation of candlenut can provide knowledge of its use in people's lives in a sustainable manner.